2008
DOI: 10.1590/s0104-530x2008000200012
|View full text |Cite
|
Sign up to set email alerts
|

Planejamento otimizado da produção e logística de empresas produtoras de sementes de milho: um estudo de caso

Abstract: Em um trabalho anterior (JUNQUEIRA; MORABITO, 2006) foi apresentado um modelo de otimização linear para auxiliar nas decisões do planejamento tático da produção, estocagem e transporte de sementes de milho, de forma a minimizar custos de produção, logísticos e fiscais, e satisfazer restrições de programação da colheita, capacidade das plantas e demanda dos clientes. O modelo foi testado apenas em situações simplificadas da realidade. No presente trabalho, analisamos a aplicação deste modelo para gerar um plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…The results obtained were compared to the managerial SIE provided by the company, from January to December 2017, according to Table 8. According to Junqueira & Morabito (2008), ICMS was considered in the total logistic cost.…”
Section: Results Of Scenariomentioning
confidence: 99%
“…The results obtained were compared to the managerial SIE provided by the company, from January to December 2017, according to Table 8. According to Junqueira & Morabito (2008), ICMS was considered in the total logistic cost.…”
Section: Results Of Scenariomentioning
confidence: 99%
“…- Junqueira & Morabito (2008, 2006 outlined in their work the importance of incorporating tax planning into logistics activities, given the complexity of the national environment;…”
Section: Optimization Models Incorporating Tax Aspectsmentioning
confidence: 99%
“…They presented a linear programming model to support medium-term planning decisions, and they report the results of the model application for a full seed corn season in this case study (more information about this case study is also found in Junqueira and Morabito (2008)). The studied enterprise experienced a rapid growth from one to four facilities in a few years.…”
Section: Production and Transportation In Multistagesmentioning
confidence: 99%
“…For more details of this company method, the reader can consult Junqueira and Morabito (2008). This comparison is illustrated in Table 3.3 and evaluates the impact of circulation taxes (scenario 1), preparing costs (scenario 2), and the combination of both (scenario 3).…”
Section: Optimizing Production and Logistics Planning In A Brazilian mentioning
confidence: 99%